Enhancement of Lecturer Professionalism using Lesson Study Approach for Curriculum Review of Mathematics 1 - Agoestanto, Arief; Kurniasih, Ary Woro; Zahid, Muhammad Zuhair; Mulyono, Mulyono (Unnes Journal of Mathematics Education, 2017)
The purpose of this research is to know the improvement of lecturer professionalism through the approach of lesson study, to see the increase of student interaction (with the students, teaching materials, lecturer), and to know whether the student learning result of the lesson study approach reaches the completeness. This research is a research of mixed method based on lesson study. Activities performed for each cycle consists of three stages: planning, execution, and reflection. The qualitative data is the description of the lectures professionality improvement with the quantitative is the increase of student interaction (with students, teaching materials, lecturers), and the result of studying Curriculum Review of Mathematics 1. The subject of this research was the students of Curriculum Review of Mathematics 1 in Mathematics Department UNNES year academic 2016/2017. The research instruments are a test, observation sheet, and questionnaire. The result of the research is the improvement of professionalism of lecturers of KBK Mathematics Education through lesson study approach for Mathematics Curriculum Mathematics 1 course, student interaction (with students, teaching materials, lecturers) increases, and learning achieves mastery.